Evaluation of the efficiency of calcium and vitamin D in treating adults with corticosteroid-induced osteoporosis: A protocol for systematic review and meta-analysis. Issue 39 (1st October 2021) - Pan, Song-Li; Li, Chen-Cui; Cui, Hong-Wang; Wang, Wen-Xian; Li, Chun-Hong
Abstract: Background: Administering corticosteroid is an effective therapeutic strategy for treating most inflammatory conditions. However, there is a chance for corticosteroid treatment to adversely affect bones, resulting in corticosteroid-induced osteoporosis, which is a highly prevalent type of secondary osteoporosis. Elevated bone resorption and reduced formation of bone are pathogenesis indicators of corticosteroid-induced osteoporosis. Preventative therapy is recommended for patients initiating steroids. This study aims to evaluate the efficiency of calcium and vitamin D in treating adults diagnosed with osteoporosis caused by corticosteroid therapy. Methods: Electronic databases will be searched systematically to source studies that have evaluated the efficiency of calcium and vitamin D as a treatment method for adult patients with osteoporosis from corticosteroid therapy. The databases include, PubMed, EMBASE, the Cochrane Library, Scopus, and Web of Science. The timeline of the search will be limited from inception to November 2020. This study will utilize the Cochrane risk of bias tool to assess the quality of the studies reviewed. Moreover, appropriate methods will be chosen to analyze the data. The RevMan 5.3 software is utilized to perform statistical analysis. Results: This study will provide additional practical and targeted results of evaluating the efficiency of calcium and vitamin D in treating adults with corticosteroid-induced osteoporosis. Conclusion: The results of this study will provide further evidence about calcium and vitamin D in treating adults with corticosteroid-induced osteoporosis, clinicians and policymakers can make practical use of the results. Ethics and dissemination: Since this systematic review does not involve any human or animal participants, an ethics approval is not required. Systematic review registration: Aug 19, 2021. osf.io/zvb38. (https://osf.io/zvb38/ ).